Psicodermatologia : autoestima e autoimagem na relação entre doenças de pele, ansiedade e depressão - Leite, Gabriela de Queiroz Cerqueira (2019)
The present study aims to analyze the relationship between self-esteem (SE) and self-image (SI) and the symptoms of anxiety and depression in patients with skin diseases. To achieve these objectives, three studies were proposed. In study 1, an integrative review of the literature was carried out in order to present evidence of the impact of skin diseases on SE and SI. Thus, 13 articles were retrieved and analyzed for their bibliometric characteristics, their methodological topics and presented content. It was observed that skin diseases cause damage to the SE and/or SI, and it was found that the more severe the disease, the greater the impact on these constructs. In the second study, also an integrative review, it was sought to gather evidence of the relationship between SE and/or SI and anxiety or depression disorders, as well as to analyze how such relations happen in varied samples, from the identification bibliometric characteristics and content of the included studies. Results of 24 articles published in the last 5 years (from January 2013 to September 2018) were collected. It was found that the lower the SE, the greater the incidence of anxious and depressive symptoms. The selected papers also revealed the predictive capacity of SE on anxious and depressive symptomatology. Regarding the possible relationships between self-image, anxiety or depression, no correlation or predictive capacity data were found in the reviewed studies. Finally, in the third study, the relationship between self-esteem, anxious and depressive symptoms in people with and without skin diseases was analyzed empirically. The study was based on the hypothesis that self-esteem tends to be lowered in the research group (RG), and that anxious and depressive symptoms are more frequent in those afflicted with a skin disease. The sample consisted of 118 people, of whom 58 were RG subjects and 60 healthy individuals (CG). The Rosenberg Self-Esteem Scale (RSES) and the Hospital Anxiety and Depression Scale (HADS) were used. In the results, it was observed that the self-esteem had lower score in the RG, but did not distinguish between the possible dermatosis, however no statistically significant difference was observed in the frequency of anxious or depressive symptomatology between the research and control groups.